2018
DOI: 10.4049/jimmunol.1701588
|View full text |Cite
|
Sign up to set email alerts
|

TLR7-Mediated Lupus Nephritis Is Independent of Type I IFN Signaling

Abstract: Systemic lupus erythematosus is an autoimmune disease characterized by increased type I IFNs, autoantibodies, and inflammatory-mediated multiorgan damage. TLR7 activation is an important contributor to systemic lupus erythematosus pathogenesis, but the mechanisms by which type I IFNs participate in TLR7-driven pathologic conditions remain uncertain. In this study, we examined the requirement for type I IFNs in TLR7-stimulated lupus nephritis. Lupus-prone NZM2328, INZM (which lack a functional type I IFN recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Other types of skin injury such as tape stripping and topical application of a TLR7 agonist have been reported to enhance kidney injury in certain lupus models, although disease enhancement was thought to be mediated by macrophages and dendritic cells rather than neutrophils 68,69 . Having demonstrated that tape stripping did not lead to neutrophil recruitment to the kidney, we propose that UV light exposure is different from other types of sterile skin inflammation and is more relevant to SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of skin injury such as tape stripping and topical application of a TLR7 agonist have been reported to enhance kidney injury in certain lupus models, although disease enhancement was thought to be mediated by macrophages and dendritic cells rather than neutrophils 68,69 . Having demonstrated that tape stripping did not lead to neutrophil recruitment to the kidney, we propose that UV light exposure is different from other types of sterile skin inflammation and is more relevant to SLE.…”
Section: Discussionmentioning
confidence: 99%
“…This inducible model was adopted to study mechanisms of TLR7 action in systemic autoimmunity, and was successfully used to investigate TLR7/TLR9 imbalance in lupus vasculopathy as well as autoimmune-mediated myocarditis (12,13). TLR7 agonism has the additional benefit of rapid onset of action, and is also being used as an accelerant in spontaneous lupus murine models (14). Herein we utilized this inducible model in WT C57BL/6j (B6) mice to determine if topical TLR7 agonism triggered significant autoimmune-mediated nephritis, since data on this is lacking in the prior publications, and we additionally tested whether it accelerates disease expression in lupus-prone NZM2410 mice.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that polymorphisms in the promoter of TLR7 were associated with SLE (Skonieczna et al, 2018). Finally, while pDCs secrete increased levels of type I IFN in a TLR7-mediated manner in SLE patients (Murayama et al, 2017), lupus nephritis was recently shown to be independent of type I IFN yet remained dependent on TLR7 signaling (Wolf et al, 2018). …”
Section: Rna Nucleic Acid Sensing In Viral Immunology and Autoimmunitymentioning
confidence: 99%